Distrust in health care and cultural factors are associated with uptake of colorectal cancer screening in Hispanic and Asian Americans. Issue 2 (4th October 2017) - Hong, Young‐Rock; Tauscher, Justin; Cardel, Michelle
Abstract : BACKGROUND: There are racial/ethnic disparities in colorectal cancer (CRC) screening, including lower uptake rates among Hispanic Americans (HAs) and Asian Americans (AAs) relative to non‐Hispanic white Americans. The objective of this study was to explore pathways associated with the use of health services and to characterize multifaceted associations with the uptake of CRC screening among HAs and AAs. METHODS: Data were obtained from the Medical Expenditure Panel Survey (2012‐2013). Participants included HA (n = 3731) and AA (n = 1345) respondents ages 50 to 75 years who met CRC screening recommendations. A modified Andersen behavioral model was used to examine pathways that lead to CRC screening uptake, including predisposing characteristics (education, economic, and cultural factors), health insurance, health needs (perceived health status and several comorbidities), and health provider contextual factors (access to care, perceived quality of health services, and distrust in health care). Structural equation modeling was used to examine the models for HAs and AAs. RESULTS: In the HA model, cultural factors (standardized regression coefficient [β] = −0.04; P = .013) and distrust in health care (β = −0.05; P = .007) directly and negatively affected CRC screening. Similarly, cultural factors (β = −0.11; P = .002) negatively affected CRC screening in the AA model, but distrust in health care was not significant ( P = .103). In both models, perceived quality of health services was positively associated with CRC screening uptake and mediated the negative association between cultural factors and CRC screening. Access to care was not associated with CRC screening. CONCLUSIONS: Correlations between CRC screening and associated factors differ among HAs and AAs, suggesting a need for multilevel interventions tailored to race/ethnicity. The current findings suggest that facilitating access to care without improving perceived quality of health services may be ineffective for increasing the uptake of CRC screening among HAs and AAs. Cancer 2018;124:335‐45 . © 2017 American Cancer Society . Abstract : Complex interrelationships are modeled between sociocultural characteristics, distrust in health care, quality of health services attributes, and the use of health services among Hispanic and Asian Americans. The results indicate that improving the perceived quality of health services could increase uptake of colorectal cancer screening in these groups.